Preliminary Report of the Oceanographical Observations of the Fifth Japanese Antarctic Research Expedition (1960-61) - Sadakiyo HORI (National Institute of Polar Research, 1962)
Bathythermograph and serial observations were performed on board the "SOYA" of the Japanese Antarctic Research Expedition (J.A.R.E.) as one of the research projects during the period of the expedition (Nov. 1960-May 1961). Bathythermograph observations were normally carried out once a day between Tokyo and Cape Town and twice a day between Cape Town and the Antarctic Region while the ship was at sea. Five hydrographic stations were occupied in the Antarctic Region, two after leaving the icy sea toward Cape Town and two in the northeastern part of the Indian Ocean on the way back to Singapore. Results of these observations are shown in the Figures and described mainly from the standpoint of physical oceanography.